Differences in patterns of care and outcomes between grade II and grade III molecularly defined 1p19q co-deleted gliomas. (February 2019) - Yeboa, Debra Nana; Yu, James B.; Liao, Eric; Huse, Jason; Penas-Prado, Marta; Kann, Benjamin H.; Sulman, Erik; Grosshans, David; Contessa, Joseph
Highlights: It is the largest series to report on 1618 1p19q co-deleted gliomas. 51% of grade II get resection alone whereas 86% of grade III get adjuvant therapy. In a propensity score matched cohort, grade was significant for survival. Hazard for death for grade III 1p19q co-deleted gliomas was about 3.6 times higher. Oligodendroglioma histology was associated with a lower likelihood of death . Abstract: Molecular markers are redefining classification of lower grade gliomas and ushering in a paradigm shift in their management. Our objective was to evaluate the differences in pattern of care and outcome by comparing grade II and grade III molecularly defined 1p19q co-deleted gliomas. We evaluated 1618 patients in the National Cancer Database diagnosed with 1p19q co-deleted gliomas from 2010 through 2014 and treated with surgery followed by radiation therapy (RT), chemotherapy (CT), or combined-modality therapy. Differences in patterns of care included that fifty-one percent of grade II tumors received surgery alone, whereas most patients with grade III tumors (86%) received surgery or biopsy followed by a form of post-operative therapy ( p < 0.001). In a propensity score matched cohort, the Cox multivariable proportional hazards model with frailty testing identified significant covariates were age, comorbidity, histology and grade. Outcomes were different in overall survival even after adjusting for treatment received. The hazard for death for grade III 1p19q co-deleted gliomas was about 3.6 times higher ([HR] 3.69, 95% confidence interval [CI] 2.03–6.68, p < 0.001) than grade II 1p19q gliomas. Oligodendroglioma histology was associated with a lower likelihood of death (HR 0.40, 95% CI 0.23–0.70, p < 0.001). Our study is among the largest series to report on 1p19q co-deleted gliomas, which would otherwise require decades to acquire outside of large databases.